Analysis of anisotropy in the upsetting process of AA2014 cast alloy embedded with fly ash. (July 2020) - Krishna, Ch Hari; Dumpala, Ravikumar; Davidson, MJ; Srinivasaraju, P; Srinivasarao, G
Developing new metal matrix composites for a wide variety of applications and analyzing the formability aspects are challenging in the area of manufacturing. In the current study, solid cylindrical samples with AA2014 as matrix material and fly ash as reinforcement were used for the investigation. AA2014 was heated to a pouring temperature of 750 ℃ and the preheated fly ash was added to the molten AA2014 in different compositions. The whole mixture was stirred to prepare composite rods of AA2014, AA2014 + 3% fly ash and AA2014 + 6% fly ash. Each set of cylindrical samples were compressed between a set of dies till fracture by employing grease, white grease and no lubrication conditions. The varying friction conditions and composition influence the anisotropy of the billets at fracture. Empirical equations were modeled to investigate the effect of anisotropy on the stress trixiality and fracture strain at the onset of fracture. The developed equation is useful in estimating critical damage constants for any material and for any lubrication condition. A correlation between damage anisotropy factor, damage constant and fracture strain was established to understand the formability limits for different anisotropy coefficients.